Children in a violent society - Osofsky, Joy D. (Guilford, 1997)
I: Scope of the problem Children and youth violence: An overview of the issue / Joy D. Osofsky * Exposure and response to community violence among children and adolescents / Esther J. Jenkins and Carl C. Bell * What children can tell us about living in a war zone / James Garbarino and Kathleen Kostelny * Firearm injuries affecting U.S. children and adolescents / Katherine Kaufer Christoffel * Media violence and youth / John P. Murray * The experience and effects of violence in infancy / Charles H. Zeanah and Michael S. Scheeringa * Incubated in terror: Neurodevelopmental factors in the "cycle of violence" / Bruce Perry * The development of violence and crime as it relates to security of attachment / Peter Fonagy, Mary Target, Miriam Steele and Howard Steele II: Prevention and intervention programs for children and families exposed to violence * Interventions with parents and caregivers of children who are exposed to violence / Betsy McAlister Groves and Barry Zuckerman * Experiencing violence in a developmental context / Steven Marans and Anne Adelman * The trauma/grief-focused group psychotherapy module of an elementary school-based violence prevention/intervention program / Lisa Murphy, Robert S. Pynoos and C. Boyd James * The Violence Intervention Project for Children and Families / Joy D. Osofsky * Perceptions of violence: Children, parents and police officers / Ana C. Fick, Joy D. Osofsky and Marva L. Lewis * Violent cities, violent streets: Children draw their neighborhoods / Marva L. Lewis and Joy D. Osofsky * Cops and kids: Issues for community policing / Pamela Jenkins, Ruth Seydlitz, Joy D .Osofsky and Ana C. Fick Prevention and policy: Directions for the future / Joy D. Osofsky